Ethnic difference of neuroendocrine regulation in women with reproductive disturbances associated with genital tuberculosis - O. Y. Leshchenko (Scientific Сentre for Family Health and Human Reproduction Problems, 2018)
Genital tuberculosis is an actual socially significant disease associated with tubal peritoneal infertility, as well as hormonal disorders of women of fertile age. Studies of the prevalence of genital tuberculosis among women with infertility in other countries and various ethnic groups have not been found, but ethnic factors must be taken into account when assessing epidemiology, causes, clinical characteristics of the course and outcomes of many diseases. The aim of the work was to establish the clinical and hormonal features of reproductive disorders associated with tuberculosis of the genital organs in women of the two main ethnic groups in the Republic of Buryatia. Hormonal features have been revealed in women with reproductive disorders and genital tuberculosis, which are characterized by a statically significant decrease in the levels of estradiol, progesterone and free testosterone in the blood serum compared to women in whom genital tuberculosis has not been verified. When analyzing ethnic characteristics, it is shown that for women with reproductive disorders associated with genital tuberculosis, a decrease in the level of ovarian hormones in the blood serum is characteristic, and also a higher level of free testosterone and a decrease in free T4 in serum for women in the Buryat ethnogroup with the Russians. Timely detection of a decrease in the level of ovarian hormones in women with reproductive disorders and genital tuberculosis will allow rational and effective correction of hypogonadism.